Zeolite and Its Potential as a Catalyst: A Study of Alternative Mineral Development in the Process of Converting Sugar Compounds into 5-Hydroxymethylfurfural - Ainun Jariyah; Veronika P. Sinta Mbia Wae; Yulius Dala Ngapa (Jurnal Kimia Sains dan Aplikasi, 2025)
Synthesis of 5-hydroxymethylfurfural (HMF) from sugar compounds in the form of glucose using natural zeolite catalysts Ende-Nusa Tenggara Timur (NTT) through activation and modification of Cr metal impregnation processes has been carried out. This study aims to determine the potential of Ende natural zeolite as a catalyst in converting sugar compounds into HMF. The results showed that natural zeolite from Ende without activation, the process of activating acid-base compounds, and zeolite with the Cr metal embedding method had the potential as a catalyst for the transformation of sugar compounds into HMF. The resulting yield of glucose substrate was around 50.17%. Using a Cr-zeolite catalyst resulted in an HMF yield for glucose substrate of 26.78%. Overall, Ende natural zeolite can be used as a catalyst for synthesizing HMF without modification and with Cr metal impregnation.